Using system-dynamic program Powersim for the population model construction (Journal of Geography and Environmental Management, 2016)
The article proposes a simplified model of population indicators developed by the system dynamics methods in the Powersim software, taking into account the migration processes. System «Population» is considered in conjunction with the natural and mechanical movement of the population. The factors influencing on the flow of migrants and natural reproduction of the population are defined. In the article described main structural elements and tools of Powersim program and their use in the construction of the population model. The role of system dynamics softwares to build various types of models are described. Created in this article a system- dynamic model allows play scenarios, options and control demographic system and such kind of model can serve as an effective tool to support decision-making processes in the field of demography and population management .
Keywords: Powersim; system-dynamic programs